Conceptual framework of biophilic design elements (BDE) for indoor work settings - Nabilah Huda Zulkifli; Abdul Razak Sapian; Putri Haryati Ibrahim (Penerbit Universiti Kebangsaan Malaysia, 2023)
The human tendency to connect with nature existed long ago. Nature and humans coexist since the beginning of time indicating that constant engagement with nature is highly needed. However, due to globalization and rapid development changes has severed this relationship between human and nature. The Industrial Revolution during the 1600s created a huge gap and disconnection between human and nature, which resulted in the depletion of mental and physical well-being as people spend long working hours indoors. The need to stay indoors to work has led to depression and mental health degradation resulting in low performance as employees disengage from their association with nature. The importance of biophilic design elements in reducing depression and mental health degradation prevailed through evidence of research abundance. However, there are still not many studies on the framework tailored to the trend of implementing nature into the indoor working environment. This paper aims to identify, compare and characterize qualitative data from various literature source on the biophilic design elements (BDE), focusing on the indoor working environment. This study will develop a conceptual framework to determine the criteria for the most prominent biophilia elements that can be implemented in indoor settings to efficiently guide professionals in the built environment in preparing the ideal work settings. The parameters from myriad studies encompass a variety of elements that are identified and classified by prominent researchers to reduce the impact of the inability to become in constant contact with nature. To improve productivity and reduce the stress level of the employees working indoors, the application of BDE contributes to the mood, performance and well-being of the employees, thus sustaining organization in the long run.